Thromboxane Responsiveness of Dog Platelets Is Inherited as an Autosomal Recessive Trait - Johnson, Gerhard J; Leis, Linda A; King, Richard A (Thrombosis and Haemostasis, 1991)
Most mongrel dogs have platelets that form thromboxane A2 (TXA2) from exogenous arachidonate, but they fail to aggregate or secrete in response to it. In contrast to these TXA2 insensitive (TXA2-) platelets, some dogs have TXA2 sensitive (TXA2+) platelets that aggregate and secrete when stirred with arachidonate. To evaluate the possible genetic basis for this difference, we carried out seven matings of mongrel dogs that yielded 48 viable offspring. Four matings of dogs with TXA2- platelets (presumed genotype TT) including 2 back-crosses, produced 32 pups with TXA2- (TT) platelets and 0 pups with TXA2+ platelets. A cross between a male with TXA2+ platelets (presumed genotype tt) and a female with TXA2+ (tt) platelets yielded 9 offspring with TXA2+ (tt) platelets and 0 with TXA2- platelets. Crossing a male presumed homozygous (TT) for TXA2- platelets with a female with TXA2+ (tt) platelets produced 2 pups with TXA2- (Tt) platelets and 0 pups with TXA2+ (tt) platelets. The same female with TXA2+ platelets crossed with a male presumed to be heterozygous (Tt) for TXA2- platelets yielded 2 pups with TXA2+ (tt) platelets and 3 pups with TXA2- (Tt) platelets. Segregation analysis of these data supports the hypothesis that the ability of dog platelets to aggregate and secrete in response to TXA2 is inherited as an autosomal recessive trait.